1995
DOI: 10.1002/jemt.1070320203
|View full text |Cite
|
Sign up to set email alerts
|

Amphibian parathyroids: Morphological and functional aspects

Abstract: Amphibians living partially or totally in a terrestrial environment are the first tetrapods to possess parathyroid glands. Purely aquatic amphibians and amphibian larvae lack these endocrine glands. The parathyroids develop at the time of metamorphosis. The parathyroid glands in caecilians consist of a single cell type, that of urodeles may be composed of basal (supporting) cells and suprabasal (chief) cells, and that of anurans of small and large chief cells. Parathyroid glands of caecilians and anurans lack … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 60 publications
(130 reference statements)
1
6
0
Order By: Relevance
“…In Xenopus , we were not able to identify the parathyroid tissue and it has previously been noted to be inconspicuous and readily degenerates [36,46]. In chicken PTH expression was also detected in the pituitary gland and in Xenopus brain/pituitary extracts, which is in agreement with studies which showed that immunoactive protein was detected in pituitaries from sheep [47], and fish [3,48] (which lack an organized parathyroid gland structure).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In Xenopus , we were not able to identify the parathyroid tissue and it has previously been noted to be inconspicuous and readily degenerates [36,46]. In chicken PTH expression was also detected in the pituitary gland and in Xenopus brain/pituitary extracts, which is in agreement with studies which showed that immunoactive protein was detected in pituitaries from sheep [47], and fish [3,48] (which lack an organized parathyroid gland structure).…”
Section: Discussionsupporting
confidence: 85%
“…Xenopus PTH was expressed in bone, kidney, lung and nervous tissue (mixed brain and pituitary). The presence of PTH family members was not established in the amphibian parathyroid gland as its small size and variable morphology made it difficult to collect [36]. …”
Section: Resultsmentioning
confidence: 99%
“…In tetrapods, calcium regulation is largely dependent on the interaction between parathyroid gland, which produces PTH, vitamin D, and cellular bone, which acts as a calcium reservoir. In contrast with fish, amphibians have functional parathyroid glands (32) and PTH receptors (33) and a vitamin D receptor (34) has recently been cloned from Xenopus . These hormone receptors, involved in calcium homeostasis, are highly homologous to those found in mammals, indicating that amphibians evolved mechanisms for controlling calcium homeostasis very similar to those found in mammals, including establishing bone as a readily available calcium reservoir.…”
Section: Discussionmentioning
confidence: 99%
“…3). The origin of parenchymal cells of this gland is common to that of the epithelial cell of the gill (see, Srivastav et al, 1995a). Why do parathyroid glands differentiate from the branchial epithelium?…”
Section: Various Circumstances In Vertebrates Other Than Fishesmentioning
confidence: 99%